2022
DOI: 10.3390/jpm12050824
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Proton Pump Inhibitors and the Risk of Incident Asthma in Patients with Coronary Artery Diseases: A Population-Based Cohort Study

Abstract: We aimed to determine the association between proton pump inhibitor (PPI) use and incident asthma in patients with coronary artery disease (CAD). This nationwide cohort study collected claims data from the Taiwanese Bureau of National Health Insurance from 2004 to 2013. The primary outcome, i.e., the risk of incident asthma, was assessed by estimating hazard ratios (HRs) and 95% confidence intervals (CIs). The adjusted HR of asthma development was estimated using the Cox regression model. Sensitivity and subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…We included the most updated meta-analyses and recent original studies. Our results are consistent with previous meta-analyses/original studies which showed a positive association between PPI and stroke 13 , lower respiratory infections 14 , falls 15 , CKD 16 , diarrheal diseases 17 , asthma 18 , 19 , pancreatic cancer 20 , Parkinson’s disease 21 , 22 , and depressive disorders 23 , 24 (Supplementary Data 2 ). Similar to the most recent meta-analyses, we also found no evidence of associations between PPI use and risk of Alzheimer’s disease 25 , colon and rectum cancer 26 , prostate cancer 27 , and breast cancer 27 .…”
Section: Discussionsupporting
confidence: 92%
“…We included the most updated meta-analyses and recent original studies. Our results are consistent with previous meta-analyses/original studies which showed a positive association between PPI and stroke 13 , lower respiratory infections 14 , falls 15 , CKD 16 , diarrheal diseases 17 , asthma 18 , 19 , pancreatic cancer 20 , Parkinson’s disease 21 , 22 , and depressive disorders 23 , 24 (Supplementary Data 2 ). Similar to the most recent meta-analyses, we also found no evidence of associations between PPI use and risk of Alzheimer’s disease 25 , colon and rectum cancer 26 , prostate cancer 27 , and breast cancer 27 .…”
Section: Discussionsupporting
confidence: 92%